China Satellite Navigation Conference (CSNC 2022) Proceedings Volume II - Yang, Changfeng; Xie, Jun.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
China Satellite Navigation Conference (CSNC 2022) Proceedings presents selected research papers from CSNC 2022 held during 22nd-25th May, 2022 in Beijing, China. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 10 topics to match the corresponding sessions in CSNC2022 which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications.
Professional GNSS Applications -- GNSS Applications for the Mass Market -- GNSS and Their Augmentations -- Satellite Orbits and Precise Positioning -- Time Frequencies and Precision Timing -- Autonomous Navigation and Intelligent Operation -- GNSS Signal Processing -- GNSS User Terminals -- PNT Architectures and New PNT Technologies -- Policies$1!+8(BStandards and Intellectual Property Rights.s
Keywords: Telecommunication; Signal processing; Aerospace engineering; Astronautics; Control engineering; Robotics; Automation; Geographic information systems; Communications Engineering, Networks; Signal, Speech and Image Processing .; Aerospace Technology and Astronautics; Control, Robotics, Automation; Geographical Information System; Artificial satellites in navigation -- Congresses; Artificial satellites in telecommunication -- Congresses